Penggunaan Tata Bahasa Yang Baik Dan Benar Dalam Penulisan Deskripsi Diri (Dd) Bagi Dys Gelombang 1 Tahun 2020 Di Universitas Dehasen Bengkulu - Fitria, Yenni; Lestari , Titje Puji; Diana, Eli; Juwita; Dina , Tri; Monica (Universitas Dehasen Bengkulu, 2019)
Professional lecturers are lecturers who have special competence in their fields to carry out teaching, research, and community service. There are four stages in lecturer certification before getting an account to register serdos, namely through D1, D2, D3 and D4. Phase D4 lecturers will get a serdos account. Later this serdos account is used to fill in the portfolio. At the stage of filling out the portfolio is entering the last stage or D5 or what is known as Self Description. The self-description assessment (DD) will determine the passing results of the Certified Lecturer (DYS). Fill in the DD by describing every activity that has been and is being carried out by DYS in a structured, good and correct language. So, whatever DYS will convey will be easily understood by the assessment team. Not only that, the contents of the DD must be in accordance with the points that have been given. Therefore, DYS requires the ability to write DD properly so that what you want to convey can be written effectively. However, not all DYS have the same ability when it comes to writing DD. Self-description value which contains 5 (five) elements, namely: development of learning quality (weight 28/100), development of knowledge/skills (weight 34/100), community service (weight 16/100), institutional management (12/100 ), and improving the quality of student activities (weight 10/100). Presenting self-descriptions must emphasize real examples that have background experience accompanied by examples, not in the form of discourse or wishes that will occur. Consistency is the strength of DYS's writing in dealing with difficult items. With consistency